Inovação no processo de incorporação de tecnologias em saúde para a Rede Ebserh - Lima, Rigeldo Augusto (2020)
Incorporation of health technologies is a central theme in the concerns of several countries today, due to their economic impact for quality of life of the populations. The fact that university hospitals in Brazil are main actors involved in effective incorporation of technologies for health care is highlighted. It is observed that, although there has been an important advance in this aspect in Brazil in recent years, incorporation of health technologies in the hospital context still lacks a structured and functional flow model. Given that Ebserh network is responsible for management of 40 University Hospitals in all regions of the country, knowing its reality on incorporation of technologies is essential for proposing a new flow. The aim of this study was to elaborate a process of incorporating health technologies for Ebserh Network. This is an applied, observational, cross-sectional study, with exploratory documentary and field research, under a descriptive analytical approach, with quantitative and qualitative data treatment. To support the generation of the main product, the research was designed in three distinct stages: stage 1 - documentary evaluation of the health products standardization commission of the Hospital Universitário de Brasília da Universidade de Brasília (HUB-UnB) and the analysis of the national documentation and literature on the subject, generating a published scientific article; step 2 - carrying out a semi-structured questionnaire to the 40 Ebserh branches to carry out a situational diagnosis of the Network and step 3 - carrying out a focus group with the members of the Health Products Standardization Commissions (HPSC) and Therapeutic Pharmacy (CTP) of the HUB-UnB, phases that underpinned the proposal for the flow model for incorporating health products, presented here as one of the products generated. As a result, it was found that the incorporation of health technologies in the University Hospitals (UH´s) studied occurs unevenly, there is no network established between the branches and not all have the conditions for the incorporation of health products to occur in an effective way, with emphasis on the absence of the Health Technology Assessment Core (HTAC) in more than half of the researched UH´s. It was concluded, from the cumulative and comparative analysis of the literature, documents and data of the field research carried out, that the new flow proposed in a guide format, composed of all the necessary steps and documentation can support the process of incorporating technologies in the hospital environment, this device stands out as a contribution to the Ebserh network, a model that is scalable to other hospital institutions in our country.